Effects of excessive energy intake and supplementation with chromium propionate on insulin resistance parameters in nonlactating dairy cows - Leiva, T. [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Aboin, A. C. [UNESP]; Drago, F. L. [UNESP]; Gennari, R. [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Amer Soc Animal Science, 2014)
The objective was to compare insulin resistance parameters in cows with adequate or excessive energy intake as well as in cows with excessive energy intake receiving Cr supplementation as chromium propionate. Thirteen multiparous, nonlactating Gir x Holstein cows were ranked by BW and BCS and assigned to 1 of 3 dietary treatments on d 0: 1) diet to meet their ME requirements without Cr supplementation (MAN; n = 4), 2) diet to exceed their ME requirements without Cr supplementation (HIGH; n = 4), and 3) HIGH with 2.5 g/d of chromium propionate (HIGHCR; n = 5, with 10 mg of Cr/cow daily). Diets were formulated to provide 100% of daily ME requirements of MAN and 177% of daily ME requirements of HIGH and HIGHCR cows and offered twice daily via individual self-locking head gates from d 0 to 88. Cow BW and BCS were recorded on d 0 and 88 of the experiment. Blood samples were collected before and 2 h after the morning feeding twice weekly. Preprandial revised quantitative insulin sensitivity check index (RQUICKI) was determined using serum glucose, insulin, and NEFA concentrations obtained before feeding. Glucose tolerance tests (GTT) were performed on d 32 and 88 by infusing cows with 0.5 g of glucose/kg of BW whereas blood samples were collected at -15, 0, 10, 20, 30, 45, 60, and 90 min relative to infusion. Change in BCS tended to be greater in HIGH and HIGHCR (P = 0.09) compared with MAN cows. Within samples collected twice weekly, serum concentrations of glucose, insulin (beginning on d 14 of the experiment), and NEFA (preprandial samples only) were greater (P <= 0.05) in HIGH compared with HIGHCR cows and tended to be greater in HIGH compared with MAN cows (P <= 0.10) but did not differ (P >= 0.52) between HIGHCR and MAN cows. Moreover, HIGH cows had reduced RQUICKI compared with MAN (P = 0.02) and HIGHCR cows (P = 0.05) whereas RQUICKI was similar between MAN and HIGHCR cows (P = 0.53). Within samples collected during the GTT, mean serum insulin concentrations and insulin: glucose ratio were greater (P < 0.01) in HIGH compared with HIGHCR cows, tended (P <= 0.09) to be greater in HIGH compared with MAN cows, and were similar (P >= 0.16) between HIGHCR and MAN cows. Serum glucose concentrations were greater (P < 0.01) for HIGH compared with MAN and HIGHCR cows 20 min relative to infusion. In conclusion, chromium propionate supplementation prevented the increase in insulin resistance caused by excessive energy intake in nonlactating dairy cows.
Keywords: chromium; dairy cows; energy intake; insulin resistance